A composite gas phase corrosion inhibitor for carbon steel and its application

By using ternary composite gas-phase corrosion inhibitors of sodium dodecyl sulfonate, bimorpholine methylurea and urea, a hydrophobic film stable on the metal surface is formed, which solves the problems of limited effects of existing gas-phase anti-rust technology and the use of toxic substances, and achieves high-efficiency and low-toxic metal anti-rust effect.

CN116837383BActive Publication Date: 2025-03-07QINGDAO XINYINGXIN PACKAGING MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310890735.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-19
Publication Date
2025-03-07
Estimated Expiration
2043-07-19

AI Technical Summary

Technical Problem

The existing gas-phase anti-rust technology has limited anti-rust effect on metal surfaces. Some products use toxic substances, and the corrosion inhibition effect of a single-component gas-phase corrosion inhibitor is poor.

Method used

A ternary composite gas-phase corrosion inhibitor of sodium dodecyl sulfonate (SLS), bimorpholine methylurea (BMMU) and urea was prepared by preparing a mixed aqueous solution with a mass ratio of 12:20:20. Using the amphiphilicity and slow volatility of SLS, a hydrophobic film stable on the metal surface was formed to prevent the erosion of corrosive ions.

Benefits of technology

It achieves efficient rust prevention of carbon steel, with a corrosion inhibition rate of 94.05%, and avoids the use of toxic substances. The product has the advantages of low toxicity, easy to obtain, uniform volatility and stable and good corrosion inhibition performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116837383B_ABST
    Figure CN116837383B_ABST
Patent Text Reader

Abstract

The present invention discloses a vapor phase corrosion inhibitor for carbon steel and a preparation method thereof. The composite vapor phase corrosion inhibitor comprises: sodium dodecyl sulfonate, bismorpholine methyl urea and urea, and the weight ratio of the three is 1~3:20~40:20~30. The vapor phase corrosion inhibitor has a significant corrosion inhibition effect on atmospheric corrosion of carbon steel and has a lasting protective effect. The raw materials of the vapor phase corrosion inhibitor provided by the present invention are easy to obtain, the preparation method is simple, and the use is convenient. The rust-proof paper prepared by the composite vapor phase corrosion inhibitor has a good rust-proof effect on carbon steel and can effectively reduce the corrosion rate of atmospheric corrosion of carbon steel. The composite vapor phase corrosion inhibitor of the present invention has the advantages of high corrosion inhibition efficiency, low toxicity, easy availability, uniform and stable volatilization, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention relates to the technical field of metal vapor phase rust prevention, and specifically refers to a composite vapor phase corrosion inhibitor based on sodium dodecyl sulfate for carbon steel, and a preparation method and application thereof. Background technology:

[0002] Metals and their products will inevitably be corroded and rusted during production, transportation and storage, especially during sea transportation and hot and humid land transportation. The commonly used anti-rust grease method is a contact anti-rust method, which is not only cumbersome, time-consuming and laborious, but also requires degreasing and cleaning before unsealing, which is very likely to cause secondary pollution to the environment. The vacuum packaging method is costly and very difficult to implement for large workpieces.

[0003] Gas phase rust prevention technology (VCI: Volatile Corrosion Inhibitor) is one of the important methods of non-contact rust prevention at present. It uses gas phase corrosion inhibitor to automatically volatilize gas at room temperature to form a protective film on the metal surface, inhibiting the occurrence of electrochemical reactions, and also blocking the erosion of the metal surface by some substances that accelerate metal corrosion, thereby slowing down or preventing the rust on the metal surface. Gas phase rust prevention technology has the characteristics of environmental friendliness, convenience of use, and cleanliness. In recent years, it has been widely used in the rust prevention of metal and its products in the production, transportation and storage of metals. Domestic gas phase rust prevention products developed based on gas phase rust prevention technology are also often reported. Gas phase rust prevention paper is one of the commonly used gas phase rust prevention products. Studies have shown that single-component gas phase corrosion inhibitors have good rust prevention properties for carbon steel, but the corrosion inhibition effect of single components is poor, and the application of gas phase rust prevention has certain limitations. At present, some formulas of commercial gas phase rust prevention products still use toxic substances such as sodium nitrite, dicyclohexylamine nitrite, and cyclohexylamine carbonate, which do not meet the requirements of green environmental protection in the new era.

[0004] Morpholine and its derivatives have almost no biological toxicity and have a long history of application as corrosion inhibitors in gas-liquid two-phase systems. Multi-component reactions have the characteristics of high atom economy, versatility, repeatability, simple steps, low energy consumption and low waste generation. It has been verified that the structure of morpholine molecules can be modified by using the three-component Mannich reaction to improve their corrosion inhibition efficiency.

[0005] Sodium dodecyl sulfate (SLS) is a widely used anionic surfactant with properties such as cleaning, wetting, foaming, and dispersing. It is widely used in washing, chemical industry, etc. due to its stable properties, wide source of raw materials, and low production cost. SLS is widely used in water-based rust-proof liquids. It can improve the dispersibility of corrosion inhibitors, promote the hydrophobicity of metal surfaces, and reduce electrochemical corrosion, but its application as a vapor phase rust-proof component has not been reported in the literature. Summary of the invention:

[0006] In view of the deficiencies of the prior art and the needs of research and application in this field, one of the purposes of the present invention is to provide a ternary composite vapor phase corrosion inhibitor based on SLS, which is prepared by preparing a mixed aqueous solution of sodium dodecyl sulfonate, bismorpholine methyl urea and urea, wherein the mass ratio of sodium dodecyl sulfonate: bismorpholine methyl urea: urea is 1-3: 20-40: 20-30; wherein sodium dodecyl sulfonate is denoted as SLS, and bismorpholine methyl urea is denoted as BMMU;

[0007] The second object of the present invention is to provide a method for preparing a composite vapor phase corrosion inhibitor based on SLS, which specifically comprises the following steps:

[0008] Step 1, according to the required mass of corrosion inhibitor, weigh SLS, BMMU and urea respectively in a mass ratio of 1-3:20-40:20-30;

[0009] Step 2, dissolving the SLS, BMMU and urea weighed in step 1 with 1 / 3 volume of distilled water respectively, stirring evenly, to obtain the desired SLS solution, BMMU solution and urea solution respectively;

[0010] Step 3, the SLS solution, BMMU solution and urea solution obtained in step 2 are allowed to stand separately, and then the three solutions are mixed and stirred evenly.

[0011] In step 1 of the preparation method, the stirring time of SLS, BMMU and urea solution is 5 to 10 minutes; the mixing temperature of the SLS solution in step 2 is 50° C.; and the temperature at which the three solutions are mixed and stirred evenly in step 3 is 50° C.

[0012] The third object of the present invention is to provide a composite vapor corrosion inhibitor based on SLS for the preparation of vapor phase anti-rust paper: neutral base paper is placed in the composite vapor phase corrosion inhibitor mixed aqueous solution, immersed at 55-120°C for 1-10 minutes, and then taken out and dried; the loading amount of the corrosion inhibitor on the surface of the obtained vapor phase anti-rust paper is 15-30g / m 2 .

[0013] The gas phase corrosion inhibitor for carbon steel provided by the present invention is prepared by uniformly mixing SLS, BMMU and urea. The present invention utilizes the amphiphilicity and slow volatilization rate of SLS and acts on the gas phase corrosion inhibitor of carbon steel for the first time. The composite gas phase corrosion inhibitor obtained by compounding the three components has multiple metal atom adsorption centers of N, O and S, which are firmly adsorbed on the metal surface. On the one hand, the hydrophilic group of SLS adsorbs the metal surface, and the hydrophobic end is arranged on the metal surface; on the other hand, SLS can improve the dispersibility of BMMU and urea in the composite components, promote the uniform and stable volatilization of the corrosion inhibition components to form a hydrophobic film on the metal surface, make it difficult to form an electrolyte film on the surface, hinder the corrosion diffusion of corrosive ions, and reduce the ability of metal electrochemical reaction and the risk of electrochemical corrosion. The corrosion inhibition rate of the anti-rust paper made of the composite gas phase corrosion inhibitor for carbon steel reaches 94.05%. The present invention provides an effective gas phase corrosion inhibitor for iron materials, which has the advantages of high corrosion inhibition efficiency, low toxicity, easy availability, uniform and stable volatilization and good corrosion inhibition performance. Description of the drawings:

[0014] Figure 1 It is an optical photograph of the gas phase identification experiment of the present invention, wherein A, B, and C are metal samples protected by a blank, a metal sample without SLS gas phase rust inhibitor, and a metal sample protected by SLS gas phase rust inhibitor, respectively.

[0015] Figure 2 These are the electrochemical test curves of blank, sample without SLS, and sample with SLS. A: impedance spectrum; B: potentiodynamic polarization curve.

[0016] Figure 3 These are the contact angle test pictures of base paper, SLS-free anti-rust paper, and SLS-containing anti-rust paper. Specific implementation method:

[0017] The present invention is described below with reference to specific examples. It will be appreciated by those skilled in the art that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention in any way.

[0018] Embodiment 1:

[0019] In this example, the corrosion inhibition efficiency obtained by volatilization reduction experiment, electrochemical impedance and dynamic potential polarization curve calculation was determined, and three factors of BMMU, SLS and urea were determined, represented by A, B and C respectively; three levels of each factor were determined; and an orthogonal comparison experimental table of three factors and three levels was established. The details are as follows:

[0020]

[0021] 1) Closed space emission reduction experiment

[0022] Experimental method: Weigh 2g of the drug, spread it evenly on a watch glass, and heat it continuously at a constant temperature of 50℃ in an oven for 72 hours. Weigh it every 24 hours and calculate the weight loss rate. The measurement results are shown in Table 1.

[0023] Table 1 Comparison of closed space volatilization reduction test results

[0024]

[0025] From the results in Table 1, it can be seen that the volatility of BMMU is relatively high. After 24 hours, the mass volatility reaches 1.63%, 2.15% after 48 hours, and 3.28% after 72 hours. It can evaporate to the metal surface in a short time, adsorb to form a film, and play a protective role. The volatility of SLS and urea is relatively weak, and the mass loss rate is less than 0.5% after 72 hours, which can effectively extend the release period of the composite corrosion inhibitor.

[0026] 2) Gas phase identification experiment

[0027] Experimental method: The experiment adopts the test tube solution method. 40mL of ionized water is used to prepare corrosion inhibitor solutions of different concentrations. The solutions are poured into the bottom of a clean glass test tube with a specification of Φ30mm×20cm. The polished carbon steel sample is hung on it and plugged with a rubber stopper. The test tube is placed in a test tube rack and then put into a 50°C oven. Each cycle is heated for 8 hours and naturally cooled for 16 hours for seven cycles. After the experiment, it is evaluated by qualitative visual inspection and weight loss method. The mass changes of the metal samples before the experiment and after the pickling solution removes the rust are recorded, and the corrosion inhibition efficiency (IE) is calculated.

[0028] Table 2 Comparison of gas phase identification experimental results:

[0029]

[0030] According to the range values ​​obtained in Table 2, the order of the influence of each factor on the test results from major to minor is: B (SLS), C (urea), A (BMMU). The larger the range, the greater the change in the value of the factor in the test range, that is, SLS has the greatest impact on the test results.

[0031] Embodiment 2:

[0032] In this example, an experimental group containing SLS, an experimental group without SLS, and a blank control experiment were used to conduct electrochemical impedance spectroscopy, potentiodynamic polarization curve testing, and meteorological identification experiments. BMMU :m 尿素 :m SLS =3:2:0.25, excluding SLS group m BMMU :m 尿素 =3:2, the total vapor phase corrosion inhibitor concentration in each group is 5.25g / L.

[0033] 1) Electrochemical experiments

[0034] Experimental method: A three-electrode system was used: the reference electrode was a saturated calomel electrode, the counter electrode was a carbon rod, and the working electrode was a homemade 45# steel electrode. Sodium sulfate solution (ω=7.1%) with or without different corrosion inhibitors was used as the electrolyte solution, in which SLS needed to be dissolved in a small amount of ethanol.

[0035] The corrosion inhibition efficiency is calculated according to the formula:

[0036]

[0037] Table 3 Electrochemical parameters

[0038]

[0039] According to the electrochemical parameters obtained in Table 3, compared with the blank, the addition of the composite vapor phase corrosion inhibitor promotes the positive shift of the corrosion potential, reduces the corrosion current density, increases the polarization resistance, inhibits the electrochemical corrosion reaction, and improves the corrosion resistance. The addition of SLS increases the corrosion inhibition efficiency obtained in the two experimental tests from 57.73% and 74.23% to 75.68% and 77.21%, respectively.

[0040] 2) Gas phase identification experiment

[0041] Experimental method: Same as the gas phase identification experiment in Example 1.

[0042] Table 4 Corrosion inhibition efficiency calculated from weight loss in gas phase identification experiment

[0043]

[0044] Compared with the blank group, the metal samples protected by the vapor phase corrosion inhibitor without SLS have significantly reduced rust, but there are still visible corrosion marks. However, the metal samples protected by the vapor phase corrosion inhibitor containing SLS have almost no rust. As shown in Table 4, the corrosion inhibition efficiency of the group containing SLS is 94.05%, which is much higher than the 75.40% of the group without SLS.

[0045] Embodiment 3:

[0046] In this example, metals protected by rust-proof paper containing SLS, rust-proof paper without SLS and blank base paper were used as experimental objects to conduct contact angle test and vapor phase corrosion inhibition ability test. Vapor phase rust-proof paper containing / without SLS was prepared by impregnation method, and the mass concentration of total vapor phase rust inhibitor in the impregnation solution was 40g / L, wherein the mass ratio of corrosion inhibitor containing SLS group in the same solvent was as follows: m BMMU :m 尿素 :m SLS =3:2:0.25, excluding SLS group m BMMU:m 尿素 =3:2.

[0047] 1) Contact angle test

[0048] Experimental method: Vapor-phase anti-rust paper containing / not containing SLS was prepared by the impregnation method. This example determines the corrosion inhibition performance of the above composite vapor-phase corrosion-inhibiting paper, which is described in detail as follows. First, the metal sample is polished to 2000# with sandpaper step by step, then washed with deionized water, degreased with alcohol, and dried with cold air. In a closed environment at 50°C, the samples were wrapped with base paper, vapor-phase anti-rust paper without SLS, and vapor-phase anti-rust base paper containing SLS for 72 hours. The contact angle was measured using a contact angle tester to study the difference in contact angles.

[0049] Table 5 Contact angle test results of metal surfaces after and after pre-filming with vapor phase anti-rust paper

[0050]

[0051]

[0052] Table 5 shows that the contact angle of the metal sample in contact with the base paper is 85.41°, the contact angle of the metal sample protected by the vapor phase anti-rust paper without SLS increases to 90.44°, and the contact angle of the metal sample protected by the vapor phase anti-rust paper with SLS increases to 96.57°. This shows that the vapor phase corrosion inhibitor successfully volatilizes to the metal surface to form a protective film, and the introduction of SLS improves the hydrophobicity of the metal surface, making it difficult to form an electrolyte film on its surface, hindering the erosion and diffusion of corrosive ions, and reducing the ability of the metal electrochemical reaction and the risk of electrochemical corrosion.

[0053] 2) Gas phase corrosion inhibition ability test experiment

[0054] Experimental method: The experimental operation refers to the national standard GB / T 35491-2017

[0055] Table 6 Evaluation results of vapor phase corrosion inhibition ability of SLS vapor phase anti-rust paper

[0056]

[0057] According to the evaluation standards in GB / T 35491-2017, as shown in Table 6, samples 1-3 are the anti-rust levels of anti-rust paper made without SLS, reaching level 1, level 1 and level 2 respectively; samples 4-6 are the anti-rust levels of anti-rust paper made with SLS, and three parallel samples have achieved level 0 anti-rust effect, proving that vapor phase anti-rust paper containing SLS has better anti-corrosion protection effect on steel.

Claims

1. A composite vapor phase corrosion inhibitor for carbon steel, characterized in that: The method is prepared by preparing a mixed aqueous solution of sodium dodecyl sulfate, bismorpholine methyl urea and urea, wherein the mass ratio of sodium dodecyl sulfate: bismorpholine methyl urea: urea is 1-3: 20-40: 20-30; sodium dodecyl sulfate is denoted as SLS, and bismorpholine methyl urea is denoted as BMMU; The preparation method of the vapor phase corrosion inhibitor is characterized by comprising the following steps: Step 1, according to the required mass of corrosion inhibitor, weigh SLS, BMMU and urea respectively in a mass ratio of 1-3:20-40:20-30; Step 2, dissolving the SLS, BMMU and urea weighed in step 1 with 1 / 3 volume of distilled water respectively, stirring evenly, to obtain the desired SLS solution, BMMU solution and urea solution respectively; Step 3, the SLS solution, BMMU solution and urea solution obtained in step 2 are allowed to stand separately, and then the three solutions are mixed and stirred evenly; The stirring time when preparing SLS, BMMU and urea solutions in step 2 of the preparation method is 5 to 10 minutes; the dissolution temperature when preparing the SLS solution is 50°C; and the temperature when the three solutions are mixed and stirred evenly in step 3 is 50°C.

2. The use of a composite vapor phase corrosion inhibitor for carbon steel according to claim 1, characterized in that The application comprises the following steps: placing neutral base paper in the composite vapor phase corrosion inhibitor mixed aqueous solution, immersing for 1-10 minutes at 55-120°C, and then taking out and drying; the loading amount of the vapor phase anti-rust paper surface corrosion inhibitor is 15-30g / m 2 .

Citation Information

Patent Citations

  • Quaternary compound gas-phase corrosion inhibitor for carbon steel and preparation method for quaternary compound gas-phase corrosion inhibitor

    CN103820785A

  • Compounded carbon dioxide corrosion inhibitor

    CN103820789A